DRYING STUDY OF EUCALYTPTUS STAIGERIANA LEAVES BY MONITORING THE HUMIDITY OF THE DRYER DISCHARGE - Braga, N. P.; Starquit, A.; Cremasco, M. A.; Brito, J. O. (Revista de Engenharia Térmica, 2005)
The drying phenomenon can be treated as simultaneous heat and mass transfer in both the light and heavy phases. In the present case, the phenomenons evolution is normally observed through the heating of and moisture removal from the heavy phase. On the other hand, while the material is heating, the light phase is cooling and humidifying. The goal of the present work is to present discharge air humidification curves as a function of the drying time for Eucalyptus staigeriana leaves drying experiments. For the air humidification measurements, a dry bulb thermocouple and relative humidity transducer were installed at both the dryer inlet and outlet. The dryer was linked to a data acquisition system, which recorded the dry bulb temperature and the relative humidity with time. These data were later used to calculate the air moisture content at the dryer inlet and outlet. The data obtained by this methodology are compared with the ones from drying kinetic (moisture content removing of the heavy phase along time), acquired by the evolution of wet material weight through the use of an analytical scale.